Creamos cuentos a partir de imágenes de nuestra comunidad - Bazalar Padilla, Gladys Violeta (2022)
The present study entitled "We create stories with images of our community", was designed and carried out in 5th grade students of primary education I.E.P. IP “Miguel Grau”. For the above, the objective of the study was to promote the creation of stories from images in our community to improve the production competence of various texts in boys and girls in the 5th grade of primary school, as well as develop communicative competence as they write. various types of texts in their mother tongue, corresponding to the Communication Area of the CNEB. For the theoretical contribution, the meaning, sequence and importance of the story, images, writing and production of texts were considered. And for the pedagogical contribution, planning processes, pedagogical and didactic techniques, evaluation and Vygotsky's theory were considered. Likewise, the methodology was active, because the students participated from the identification of the learning problem, development and closure of the proposed study. For this, it was designed as an alternative and to solve the problem, the creation of stories with the use of images was used, the same one that helped to promote the participation and motivation of the students, in addition, socialization, collaboration, skills and writing skills in text production.